Crystal structures of human peroxiredoxin 6 in different oxidation states - Kim, Kyung Hee; Lee, Weontae; Kim, Eunice EunKyeong (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2016)
Peroxiredoxins (Prxs) are a family of antioxidant enzymes found ubiquitously. Prxs function not only as H2O2 scavengers but also as highly sensitive H2O2 sensors and signal transducers. Since reactive oxygen species are involved in many cellular metabolic and signaling processes, Prxs play important roles in various diseases. Prxs can be hyperoxidized to the sulfinic acid (-SO2H) or sulfonic acid (-SO3H) forms in the presence of high concentrations of H2O2. It is known that oligomerization of Prx is changed accompanying oxidation states, and linked to the function. Among the six Prxs in mammals, Prx6 is the only 1-Cys Prx. It is found in all organs in humans, unlike some 2-Cys Prxs, and is present in all species from bacteria to humans. In addition, Prx6 has Ca2+-independent phospholipase A(2) (PLA(2)) activity. Thus far only the crystal structure of Prx in the oxidized state has been reported. In this study, we present the crystal structures of human Prx6 in the reduced (SH) and the sulfinic acid (SO2H) forms. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: S-TRANSFERASE-PI; 1-CYS PEROXIREDOXIN; 2-CYS PEROXIREDOXINS; PEROXIDASE; ENZYMES; PHOSPHORYLATION; FEATURES; CYSTEINE; COMPLEX; SUITE